2020
DOI: 10.1002/pbc.28785
|View full text |Cite
|
Sign up to set email alerts
|

A review of the clinical applications of ketamine in pediatric oncology

Abstract: Ketamine is a dissociative anesthetic agent with excellent analgesic properties and a favorable safety profile. The feasibility and efficacy of various routes of administration have been established, including intravenous (IV), intramuscular (IM), oral, intranasal, rectal, and transdermal routes. The advent of newer anesthetic agents has led to a decline in the use of ketamine as an anesthetic, but its utility in short-term sedation and analgesia has expanded. Its value for chronic pain management in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 110 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Complications of ketamine-based anesthesia in children radiotherapy were 23 -24% in previous studies, comprising inadequate movement control, sialorrhea, and slow recovery (7,33). Furthermore, ketamine had the highest number of complications in a recently conducted review with a 24% overall rate (7,33). Our study used ketamine intramuscular, and ketamine + midazolam was the leading cause of delay in consciousness return, insufficient motionlessness, nausea, vomiting, and patient discharge from the recovery.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Complications of ketamine-based anesthesia in children radiotherapy were 23 -24% in previous studies, comprising inadequate movement control, sialorrhea, and slow recovery (7,33). Furthermore, ketamine had the highest number of complications in a recently conducted review with a 24% overall rate (7,33). Our study used ketamine intramuscular, and ketamine + midazolam was the leading cause of delay in consciousness return, insufficient motionlessness, nausea, vomiting, and patient discharge from the recovery.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the anesthesia technique was modified from intravenous approach to Intra muscle technique (IM ketamine). Complications of ketamine-based anesthesia in children radiotherapy were 23 -24% in previous studies, comprising inadequate movement control, sialorrhea, and slow recovery (7,33). Furthermore, ketamine had the highest number of complications in a recently conducted review with a 24% overall rate (7,33).…”
Section: Discussionmentioning
confidence: 94%
“…The administration of general anesthesia alone is known to impair immune function; however, the addition of pectoral nerve II block under general anesthesia increases the proportion of NK cells, improves tumor cell killing activity, and upregulates postoperative IL-2 concentration in patients’ plasma ( 42 ). Ketamine, a dissociative anesthetic agent with excellent analgesic properties and a favorable safety profile, effectively reduces postoperative pain, blunts hyperalgesia, lowers opiate consumption, and even decreases chronic persistent postoperative pain ( 43 , 44 ). However, ketamine has tumor modulatory and anti-inflammatory effects, including, promoting tumor growth via decreasing NK cells and increasing tumor cell retention ( 35 ) and generally inducing immunosuppression ( 45 ).…”
Section: Perioperative Factors Associated With Cancer Promotionmentioning
confidence: 99%
“…1 The efficacy of various routes of administration such as intravenous, intramuscular, oral, intranasal, rectal, and transdermal has been proven. 2 The high-dose intravenous form of ketamine is used clinically in short-term surgical procedures, and the low dose is used to create an analgesic effect. 3,4 It has been shown that ketamine at sub-anesthetic doses has rapid, strong antidepressant effects in patients with resistant depression.…”
Section: Introductionmentioning
confidence: 99%